Dyskryminacja w środowisku szkolnym - perspektywa uczniów technikum = Discrimination in the school environment ? the perspective of technical school students - Szydłowska, Karolina; Ćwirynkało, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The school environment, like many others, is not free from discriminatory attitudes, stereotypesand other barriers that prevent various groups from fully participating in school life. The research discussed in this chapter has been embedded in the interpretative paradigm. Using a soft qualitative approach and interpretive phenomenological analysis, 17 interviews were conducted with students of the fourth year of a technical secondary school. The aim of the research was to understand how the students perceive the phenomenon of discrimination. The findings refer to such areas as: meanings attributed to discrimination, perpetrators, victims, causes and forms of discrimination, students` reactions to the phenomenon of discrimination, as well as anti-discriminatory activities undertaken in the school environment. Based on the analysis of the research material, a number of recommendations for practice are made.
Keywords: dyskryminacja; szkoła; uczniowie szkół ponadpodstawowych; edukacja antydyskryminacyjna; interpretacyjna analiza fenomenologiczna; discrimination; school; post-primary school students; antidiscriminatory education; interpretative phenomenological analysis